The expanding roles of endoplasmic reticulum stress in virus replication and pathogenesis. (June 2015) - Li, Shanshan; Kong, Lingbao; Yu, Xilan
Abstract The endoplasmic reticulum (ER) is a cellular membrane organelle that plays important roles in virus replication and maturation. Accumulating evidence indicates that virus infection often disturbs ER homeostasis and leads to ER stress, which is associated with a variety of prevalent diseases. To cope with the deleterious effects of virus-induced ER stress, cells activate critical signaling pathways including the unfolded protein response (UPR) and intrinsic mitochondrial apoptosis, which have complex effects on virus replication and pathogenesis. In this review, we present a comprehensive summary of recent research in this field, which revealed that about 36 viruses trigger ER stress and differentially activate ER stress-related signaling pathways. We also highlight the strategies evolved by viruses to modulate ER stress-related signaling networks including immune responses in order to ensure their survival and pathogenesis. Together, the knowledge gained from this field will shed light on unveiling the mechanisms of virus replication and pathogenesis and provide insight for future research as well as antiviral development.